PENGUJIAN KERENTANAN SISTEM DENGAN MENGGUNAKAN METODE PENETRATION TESTING DI UNIVERSITAS XYZ - Ginting, Jusia Amanda; Ngurah Suryantara, I Gusti Gusti (Infotech: Journal of Technology Information, 2021)
Awareness of information security will be a priority in the event of data loss or damage. This certainly harms the performance of a company or organization due to unpreparedness to resolve or minimize risks that can occur. The impact that occurs on the security system used is that the system cannot provide a sense of security because the system used and has security holes that can be used to exploit systems and networks at XYZ University. This study aims to examine the internal and external security controls of the system by identifying threats that can pose serious problems to assets at XYZ University by using the penetration testing method, the results can be used as a benchmark in measuring the weaknesses of the network and system from external attacks. The goal is to implement preventive controls against risks that can occur to improve system security at XYZ University.